2010
DOI: 10.2737/psw-gtr-231
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of managing vegetation in conifer plantations in northern and central California: results, application, principles, and challenges

Abstract: The Forest Service of the U.S. Department of Agriculture is dedicated to the principle of multiple use management of the Nation's forest resources for sustained yields of wood, water, forage, wildlife, and recreation. Through forestry research, cooperation with the States and private forest owners, and management of the National Forests and National Grasslands, it strives-as directed by Congress-to provide increasingly greater service to a growing Nation.The U.S. Department of Agriculture (USDA) prohibits disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…"release") in the first five years. In areas where planted trees are more widely spaced, drought stress can be exacerbated by the rapid growth of shrubs and grasses in the high-light environment between trees and increase competition for nutrients and soil moisture, (Lanini and Radosevich, 1986;Riegel et al, 1992;McDonald and Fiddler, 2010;Bohlman et al, 2016). Competing vegetation is reduced manually, mechanically, or with herbicides.…”
Section: Current Reforestation Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…"release") in the first five years. In areas where planted trees are more widely spaced, drought stress can be exacerbated by the rapid growth of shrubs and grasses in the high-light environment between trees and increase competition for nutrients and soil moisture, (Lanini and Radosevich, 1986;Riegel et al, 1992;McDonald and Fiddler, 2010;Bohlman et al, 2016). Competing vegetation is reduced manually, mechanically, or with herbicides.…”
Section: Current Reforestation Practicesmentioning
confidence: 99%
“…Managers are primarily concerned that competing vegetation reduces regeneration growth rates, lengthens the time required for trees to reach a size resistant to surface fires, and favors conifer species that are more shade-tolerant yet sensitive to fire and drought, such as white fir (Abies concolor) and incense cedar (Calocedrus decurrens) (McDonald and Fiddler, 2010).…”
Section: Drivers Of Successful Conifer Regenerationmentioning
confidence: 99%
“…Another component of postfire treatment can include the use of herbicides to reduce shrubs and favor conifer survival and growth (McDonald andFiddler 2010, Zhang et al 2008). A study comparing active postfire management to passive management on private forest lands that burned in the large Fountain Fire (1992) in the synthesis area concluded that active postfire reforestation treatments were more effective at quickly restoring forest cover than passive management (Zhang et al 2008).…”
Section: Reforestation-mentioning
confidence: 99%
“…Tree planting can be an important component of forest management and restoration, particularly following severe wildfires and intensive timber harvest (McDonald and Fiddler 2010).…”
Section: Seed Source Selectionmentioning
confidence: 99%